Quantitative ethnomedicinal study and conservation status of medicinal flora used by the indigenous peoples of Sultan Khail valley, Dir Upper, Pakistan - K. Rahman (6794081) (2023)
The present study was conducted to explore the ethnomedicinal uses, quantitative analysis and conservation status of medicinal flora of Sultan Khail valley, Dir Upper, Pakistan. The data was collected during 2017-2019 using a semi-structured questionnaire. Ethnomedicinal uses of plant species were determined and the plant species were classified based on habits, parts used, and method of preparation of remedies. Frequency of citation (FC), relative frequency of citation (RFC) and family importance values (FIV) were calculated. The plant species were assessed for their conservation status as per IUCN standard criteria. The inhabitants of the Sultan Khail valley use 88 plant species belonging to 57 families for the treatment of different human diseases. Lamiaceae was the dominant family represented with 8 medicinal species (9%) followed by Rosaceae (5 species, 6%). The most commonly used plant parts were leaves (33.1%) followed by fruits (16.1%), while the main method of remedy preparation was decoctions (33.3%). The highest RFC value was recorded for Geranium wallichianum (0.47), followed by Berberis lycium (0.44). Lamiaceae was the most cited family (FIV, 231), followed by Polygonaceae (73). Five plant species were found to be endangered, 39 species were vulnerable, 32 species were rare, and 12 species were found to be infrequent. The medicinal flora of the area is under severe biotic pressure and needs proper conservation; otherwise, they will be lost in the near future. Other Information Published in: Brazilian Journal of Biology License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1590/1519-6984.267583